Uptake and transport of B12-conjugated nanoparticles in airway epithelium - Fowler, Robyn; Vllasaliu, Driton; Falcone, Franco H.; Garnett, Martin; Smith, Bryan; Horsley, Helen; Alexander, Cameron; Stolnik, Snow (Elsevier, 2013)
Non-invasive delivery of biotherapeutics, as an attractive alternative to injections, could potentially be achieved through the mucosal surfaces, utilizing nanoscale therapeutic carriers. However, nanoparticles do not readily cross the mucosal barriers,with the epitheliumpresenting a major barrier to their translocation. The transcytotic pathway of vitamin B12 has previously been shown to ‘ferry’ B12-decorated nanoparticles across intestinal epithelial (Caco-2) cells. However, such studies have not been reported for the airway epithelium. Furthermore, the presence in the airways of the cell machinery responsible for transepithelial trafficking of B12 is not widely reported. Using a combination of molecular biology and immunostaining techniques, our work demonstrates that the bronchial cell line, Calu-3, expresses the B12-intrinsic factor receptor, the transcobalamin II receptor and the transcobalamin II carrier protein. Importantly, the work showed that sub-200 nm model nanoparticles chemically conjugated to B12 were internalised and transported across the Calu-3 cell layers,with B12 conjugation not only enhancing cell uptake and transepithelial transport, but also influencing intracellular trafficking. Our work therefore demonstrates that the B12 endocytotic apparatus is not only present in this airway model, but also transports ligand-conjugated nanoparticles across polarised epithelial cells, indicating potential for B12-mediated delivery of nanoscale carriers of biotherapeutics across the airways.